Biomineralization in bryozoans: present, past and future. (4th November 2014) - Taylor, Paul D.; Lombardi, Chiara; Cocito, Silvia
ABSTRACT Many animal phyla have the physiological ability to produce biomineralized skeletons with functional roles that have been shaped by natural selection for more than 500 million years. Among these are bryozoans, a moderately diverse phylum of aquatic invertebrates with a rich fossil record and importance today as bioconstructors in some shallow‐water marine habitats. Biomineralizational patterns and, especially, processes are poorly understood in bryozoans but are conventionally believed to be similar to those of the related lophotrochozoan phyla Brachiopoda and Mollusca. However, bryozoan skeletons are more intricate than those of these two phyla. Calcareous skeletons have been acquired independently in two bryozoan clades – Stenolaemata in the Ordovician and Cheilostomata in the Jurassic – providing an evolutionary replicate. This review aims to highlight the importance of biomineralization in bryozoans and focuses on their skeletal ultrastructures, mineralogy and chemistry, the roles of organic components, the evolutionary history of bimineralization in bryozoans with respect to changes in seawater chemistry, and the impact of contemporary global changes, especially ocean acidification, on bryozoan skeletons. Bryozoan skeletons are constructed from three different wall types (exterior, interior and compound) differing in the presence/absence and location of organic cuticular layers. Skeletal ultrastructures can be classified into wall‐parallel (i.e. laminated) and wall‐perpendicular (i.e. prismatic) fabrics, the latter apparently found in only one of the two biomineralizing clades (Cheilostomata), which is also the only clade to biomineralize aragonite. A plethora of ultrastructural fabrics can be recognized and most occur in combination with other fabrics to constitute a fabric suite. The proportion of aragonitic and bimineralic bryozoans, as well as the Mg content of bryozoan skeletons, show a latitudinal increase into the warmer waters of the tropics. Responses of bryozoan mineralogy and skeletal thickness to oscillations between calcite and aragonite seas through geological time are equivocal. Field and laboratory studies of living bryozoans have shown that predicted future changes in pH (ocean acidification) combined with global warming are likely to have detrimental effects on calcification, growth rate and production of polymorphic zooids for defence and reproduction, although some species exhibit reasonable levels of resilience. Some key questions about bryozoan biomineralization that need to be addressed are identified.